Σκέψεις για δύο μεσαιωνικά τοπωνύμια της Κριμαίας (Αλούστου, Παρθενίται) - ΧΑΡΑΛΑΜΠΑΚΗΣ Παντελής (Byzantina Symmeikta, 2014)
In the present study the author tries to examine two medieval place names of the Crimea: Aloustou (Ἀλούστου) and Parthenitai (Παρθενίται). The Greek name Aloustou is in genitive and it should originally be a place name formed by a personal name or rather a nick name aloustos (ἄλουστος). In the late Middle Ages the name changed to Alusta (Ἀλούστα), thus becoming a female one. The loss of the initial a- in the name (Lusta) attested in some Latin and Italian documents can be explained. The name Parthenitai (in plural) is actually a place name formed by an ethnic name Parthenitai. The ethnic name derived from a place name Parthenion (Παρθένιον). In the late Middle Ages the name Parthenitai also changed to a female one, Parthenita (Παρθενίτα).